The Influence of Convenience, Trust, Risk Literacy on Decisions to Use Shopee PayLater (Student Case Study) - Widiyani Hasibuan; Saparuddin Siregar; Fauzi Arif Lubis (Electronic Journal of Education, Social Economics and Technology, 2025)
The purpose of this study is to investigate how students' decisions to use the Shopee PayLater feature are influenced by ease of use, trust, and risk literacy. Using a quantitative approach, this research was carried out as a field study with a population of students who have tried or used the service; the sample consisted of 100 respondents, and data was gathered through questionnaires and analyzed using simple linear regression. The results show that risk literacy, trust, and ease of use, both separately and together, significantly influence students' decisions to use Shopee PayLater.